Al-Furuq Al-Lughowiyah dan Pengaruhnya dalam Penafsiran (Studi Analisis Perbedaan Makna Kosakata dalam Al-Qur’an) - Wanty Yustiana (Departement of Mathematics Education, 2024)
Al-Furuq is the most important material in linguistics raised by linguists from groups who do not agree with Taraduf in Arabic. The discussion of Al-Furuq (differences in the meaning and use of words), has its own special features, by studying it someone will arrive at the true meaning and meaning of a word, by mastering it someone will analyze the clear differences of several words that look the same, so that he will never be mistaken again in the use and selection of vocabulary in the language of communication he uses. In terms of general understanding, for the lower to middle strata of society there are not too many who criticize, but for some others, especially religious leaders and educated people, there are still those who question the truth of the meaning and content of the translation. On this basis, the researcher wants to contribute to increasing people's understanding of the Qur'an through the Lughowi aspect, namely from the perspective of Al-Furuq Al-Lughowiyah. The results of this study indicate that several lafadz in the Qur'an have differences both in terms of their use and context. In a letter in the Qur'an where the context of discussion is different, each lafadz gives a different meaning, this difference is adjusted according to the context of the discussion. If there are several words that have different but close meanings, then the meaning must still be different. Researchers can illustrate that indeed there are no words that really have the exact same meaning. So it is not always possible to use it in the same sentence context.